Regions in International Trade - Stanisław Umiński; Jarosław M. Nazarczuk (Regions in International Trade, 2021)
The book provides a comprehensive approach to the assessment of the nature of exporting activity, combining well-established theoretical reasoning with empirical evidence, and also signalling important economic policy recommendations. It is suitable for a wide range of recipients, ranging from scholars and students, to policy-makers or local/regional authorities engaged in the process of designing/implementing regional policies. Regional authorities show more interest in export potential because globalisation makes the regional economies more open and vulnerable to external economic shocks. The international trade channel has become an important factor influencing the region's economic performance, including dynamics and volatility of economic growth as well as labour market performance. Due to economic transition and the accession to the EU, Poland's regions have become more open than ever. For regions of both Poland and Spain (an EU country similar to Poland in terms of size and the number of administrative units), being part of the EU's internal market with a free circulation of goods and capital - exerts competitive pressure, which can be regarded a stress test showing the regional adaptive capacity and competitiveness. Apart from the in-depth review of the regional export activity of Poland and Spain, the book also provides similar insights for Canada and Australia, in terms of their regional export performance and trade policy. About authors: Stanisław Umiński (PhD), professor at the University of Gdansk, Department of International Economics and Economic Development. Co-founder and vice-president of the Institute of Development. BI consultant, ABSL, Poland. Participant and head of research projects on FDI, foreign trade and regional development, carried on for instance for European Commission, National Bank of Poland, Ministry of Regional Development, National Science Centre. Author and co-author of publications in the fields of FDI, competitiveness, the foreign trade of regions and special economic zones. Jarosław M. Nazarczuk (PhD), assistant professor at the Faculty of Economic Sciences of the University of Warmia and Mazury in Olsztyn. Participant of research projects concerning: operation of special economic zones, regional export activity, the role of institutions in firms' location decisions, economic development of selected regions, evaluation of regional operational programmes, high-tech clusters, regional marketing, financed from National Science Centre or carried for regional marshals' offices and other public entities. Author and co-author of publications on SEZs, regional export performance, FDI, smart specialisation, location determinants, public aid effectiveness
10.1515/9788395815041; 10.1515/9788395815041